To compare the effect of acupuncture and acupuncture with moxibustion on pain in patients with chronic osteoarthritis of knees: A randomized control study - Sabeetha S; Sujithra TS; Mangaiyarkarasi N; Manavalan N; Prabu P (Indian Journal of Integrative Medicine, 2024)
Background: Osteoarthritis is a chronic progressive musculoskeletal disorder characterized by stiffness, pain and impaired movement. Acupuncture and moxibustion has an influence on the pain management and range of motion in knee osteoarthritis patients. However, there is no study to find effectiveness between the acupuncture and moxibustion with that of acupuncture alone, this study was evaluated to find the comparison between the two interventions. Thus, the aim of the study is to compare the effect of Acupuncture with Moxibustion and only Acupuncture on pain management in chronic osteoarthritis of knees. Materials and Methods: 80 subjects with chronic knee osteoarthritis were randomly assigned into study and control group based on the inclusion and exclusion criteria. All the study group received treatment of acupuncture with moxibustion on acupuncture points GB-34, UB-40, K-10, St-36 and Liv-7. Control group received treatment of acupuncture points same points without moxibustion for 20 minutes 6 days in a week for 2 weeks. Baseline and post-test assessments of WOMAC (Western Ontario and Mc Master Universities index) and Range of Motion (ROM) were measured just before and immediately after 2 weeks of intervention. Statistical analysis was done using Statistical Package for Social Sciences (SPSS) software Version 21.0 (Armonk, NY: IBM Corp) value α=0.05 level was considered as significant. Results: Results of this study showed a significant reduction of WOMAC score and increased ROM in both study and control group. Between groups analysis showed a significant reduction in study group than control group. Conclusion: The present study demonstrated that acupuncture with moxibustion is effective in pain management and improving ROM than acupuncture only group KOA (knee osteoarthritis) patients.